Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan Perusahaan di Bidang Industri Tekstil yang Terdaftar di BEI - Mirana Lavenia; Octavia Dwi Sagita Sari; Putri Nadiya Puspitasari; Imeltiana Imeltiana; Cholis Hidayati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research aims to conduct a financial ratio analysis of four textile companies in Indonesia, namely PT Argo Pantes, PT Century, PT Ever Shine, and PT Trisula, during the 2019-2021 period. By considering the impact of the COVID-19 pandemic, this research uses a quantitative approach with a descriptive study. The results of the liquidity ratio analysis show that PT Trisula has the best ability to fulfill short-term obligations. In terms of activity, PT Ever Shine stands out in collection turnover, while PT Century has the highest inventory turnover. The solvency ratio shows that PT Trisula has the lowest dependence on debt, while PT Argo Pantes needs to pay attention to its debt structure. In terms of profitability, PT Ever Shine stands out with the highest profit margin, while PT Argo Pantes and PT Century experience negative margins. Market analysis shows a good valuation for PT Trisula with a high PER. Strategy recommendations are provided for each company, including improving debt structure, operational strategy, and dividend policy.